Hirschsprung-associated enterocolitis: Observational study in a paediatric emergency care unit - Margarita Sellers; Clara Udaondo; Bárbara Moreno; Gonzalo Martínez-Alés; Jesús Díez; Leopoldo Martínez; María de Ceano-Vivas (Elsevier, 2018)
Introduction: Hirschsprung-associated enterocolitis is a significant cause of morbidity and mortality in infants with Hirschsprung's disease. The fact that the symptoms are so variable and unspecific leads to a slow or incorrect diagnosis. The purpose of this study is to identify clinical factors associated with the diagnosis, as well as to evaluate the subsequent management of children with suspected Hirschsprung-associated enterocolitis in a paediatric emergency department. Material and methods: A retrospective descriptive study was conducted on patients with Hirschsprung's disease who were seen in a paediatric emergency department between April 2011 and November 2015 due to clinical symptoms compatible with enterocolitis. An analytical multivariate analysis was also performed on the epidemiological and clinical variables associated to enterocolitis. Results: A total of 75 consultation episodes in the Paediatric Emergency Department were studied, of which 52% (39) were finally diagnosed as enterocolitis. Overall, diarrhoea was the most frequent reason for consultation (74.7%). Lethargy, abdominal distension, and pathological findings on the X-ray showed a significant association with the diagnosis of Hirschsprung-associated enterocolitis. Hospital admission rate was 77.3%. Conclusion: Hirschsprung-associated enterocolitis should be considered in all children with Hirschsprung's disease that consult the Emergency Department, especially those with gastrointestinal symptoms associated with lethargy, abdominal distension and pathological findings on the X-ray. The therapeutic diagnostic process should be initiated as soon as possible, either by clinical observation, if there are any doubts, or by medical treatment if there is a high clinical suspicion. Resumen: Introducción: La enterocolitis asociada a la enfermedad de Hirschsprung es su complicación más grave y conlleva una importante morbimortalidad. Se presenta con síntomas inespecíficos que dificultan el diagnóstico. Este trabajo pretende identificar, en pacientes con clínica compatible que acuden a un servicio de urgencias pediátricas, los factores clínicos asociados a enterocolitis asociada a enfermedad de Hirschsprung y evaluar su manejo posterior. Material y métodos: Estudio retrospectivo descriptivo de los pacientes con enfermedad de Hirschsprung que acudieron al Servicio de Urgencias Pediátricas entre abril de 2011 y noviembre de 2015 con clínica digestiva compatible con enterocolitis. Análisis uni y multivariante de las variables epidemiológicas y clínicas asociadas al riesgo de padecer enterocolitis. Resultados: Se estudiaron un total de 75 episodios de consulta, de los que un 52% (39) fueron finalmente catalogados de enterocolitis. Globalmente, la diarrea fue el motivo de consulta más frecuente (74,7%). La presencia de letargia, distensión abdominal y alteraciones en la radiografía de abdomen demostró una asociación estadísticamente significativa con el diagnóstico de enterocolitis asociada a enfermedad de Hirschsprung. Se realizó ingreso hospitalario en el 77,3% de los casos. Conclusión: La enterocolitis asociada a la enfermedad de Hirschsprung debe tenerse en cuenta en todos aquellos pacientes con enfermedad de Hirschsprung que consulten en Urgencias por síntomas digestivos, especialmente si asocian letargia, distensión abdominal o hallazgos patológicos en la radiografía de abdomen. Se debe iniciar el proceso diagnóstico-terapéutico precozmente, ya sea con observación clínica si existen dudas diagnósticas o con tratamiento médico si existe una alta sospecha clínica.